Digital Literacy Implementation Strategy in Social Studies Learning in Elementary Schools - Yuliani, Meri; Habibi, Muhamad Ridwan (JUPE : Jurnal Pendidikan Mandala, 2025)
The development of information and communication technology in the digital era has had a significant impact on education, including in the learning of Social Studies (IPS). Digital literacy is an essential 21st-century skill that students must possess to access, evaluate, and utilize information critically and responsibly. This research employed a qualitative, descriptive approach. Subjects were selected purposively. Data collection techniques included interviews, observation, and documentation. Data analysis employed the interactive model of Miles Huberman and Saldana. Data validity was validated using source and technique triangulation. The results of this study are as follows: Strategies to increase the number and variety of quality learning resources include providing digital reading materials such as e-books and encyclopedias, educational websites like Ruang Guru and Quipper, learning applications like Quizizz and Wordwall, and school and classroom bulletin boards as literacy resources.